A Guide to Delivering Good Asset Management in the Road Sector through Performance Based Contracting - Gericke, Ben; Henning, Theuns; Greewood, Ian (World Bank, Washington, DC, 2014)
The road sector represents a significant asset to any country both in terms of the physical cost to build it, and the social and economic benefits that it facilitates. Good asset management in the road sector is about obtaining the desired benefits at the least whole-of-life cost, and it is therefore natural to seek to implement a robust asset management approach on what is typically a nation's largest asset. Implementation of performance based contracting (PBC) necessitates the identification of many of the cornerstones to asset management, such as knowing the asset, managing risks, and determining the sustainable level of service for the funds available. The aim of this guide is to help understand: (1) what asset management is and why it is important; (2) how performance based contracting delivers good asset management; and (3) the issues and challenges associated with successful implementation of a performance based contract. This guide is focused on PBCs with a significant contract term. This guide draws extensively on the report, review of performance based contracting in the road sector, phase 1: tasks 1 to 6 which examined 35 projects across 27 countries, combined with the knowledge of an international project team.